2018
DOI: 10.1080/03630242.2018.1434589
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in driving under the influence (DUI) program client characteristics: Implications for treatment delivery

Abstract: The purpose of this descriptive study was to examine gender differences in the characteristics of clients in a large Driving Under the Influence (DUI) program in Southern California. We analyzed secondary de-identified data from a large DUI program for the years 2009-2014 (n = 19,619). Sociodemographic characteristics, measures of physical and mental comorbidity, and alcohol use severity measures were compared for male and female clients. Women averaged 32.85 years of age (SD = 10.70), while men were slightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…While there were limited substance use differences, females in the current study were significantly more likely to report mental health problems, which is similar to findings from other studies of nonrural DUI offenders . The rates in the current study are comparable to those found in previous research focused on other rural drug‐using female offenders .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…While there were limited substance use differences, females in the current study were significantly more likely to report mental health problems, which is similar to findings from other studies of nonrural DUI offenders . The rates in the current study are comparable to those found in previous research focused on other rural drug‐using female offenders .…”
Section: Discussionsupporting
confidence: 86%
“…Recent research has highlighted the increasing number of female drivers who are arrested for driving under the influence (DUI) . As a result, more studies have focused on understanding sex differences among DUI offenders to identify the unique characteristics and needs of female impaired drivers . For example, female DUI offenders are more likely to use substances daily, meet drug use disorder criteria, and have co‐occurring mental health problems compared with male DUI offenders.…”
Section: Introductionmentioning
confidence: 99%
“…This gender distribution mirrors that identified for Types I and II alcoholism; Type II alcoholism is more prevalent among men than women (Cloninger et al, 1996; Del Boca and Hesslebrock, 1996). This distribution also supports prior work in this area (Reilly et al, 2018) as well as prior work with this sample (LaPlante et al, 2008) that finds that female repeat DUI offenders tend to have a more severe profile of mental health issues than male repeat DUI offenders.…”
Section: Discussionsupporting
confidence: 82%
“…A growing body of research has demonstrated that female impaired drivers constitute a distinct subpopulation of impaired drivers. Compared to males, studies have shown that female impaired drivers are more likely to report psychiatric disorders, such as anxiety, bipolar, or depressive disorders (Maxwell and Freeman 2007;Reilly et al 2019). This is consistent with the higher prevalence of anxiety and mood disorders among women that has been documented in the general population across cohorts from different countries (Seedat et al 2009).…”
Section: Introductionsupporting
confidence: 62%